Nursing diagnosis - Szewczyk, Maria T. (Przewodnik Lekarza/Guide for GPs, 2006)
Main role in both theory and practice of nursing plays nursing process – well known method of work with patient. This term was first implemented in the 50’ of XX century. Nursing process is a scientific approach to making appropriate decisions and effective resolving of medical problems. Fundamental part of this process is nursing diagnosis which is connected with assessment of current and potential problems. This method leads to planning and implementing effective activities of care.